1991
DOI: 10.1073/pnas.88.7.2638
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent induction of resistance to terminal differentiation in x-irradiated cultures of normal human keratinocytes.

Abstract: Epidermal cell clones able to proliferate under conditions that cause normal human foreskin keratinocytes (NHK) to terminally differentiate were obtained in a dosedependent fashion after repeated x-irradiation. No terminal differentiation-resistant (TDR) clones were detected unless the total x-ray dose was split in several fractions given at protracted intervals. The x-ray-induced TDR cells were aneuploid and differed from growing NHK with regard to expression of specific protein markers of differentiation. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The simian virus 40-transformed newborn human kidney cell line NB-E (45), its derivative NB324K, and A9, a subline of mouse L cells (29), were grown in minimal essential medium (GIBCO), as were the human cervical carcinoma cell line HeLa, the spontaneously immortalized human keratinocytes HaCat (4), the simian virus 40-trans-formed human lung fibroblast line MRC5-V1 (26), the y-6'Cotransformed human fibroblast line KMST6 (33), and NHF-5, a normal, finite-life human foreskin fibroblast strain derived from a primary culture (infected at passage 4 or 5). Normal nondifferentiated human keratinocytes (NHK) were isolated from neonatal foreskins by the method of Tuynder et al (53). NHK cells were grown in (serum-free) keratinocyte-SFM medium (GIBCO) and infected at passages 1 or 2.…”
Section: Methodsmentioning
confidence: 99%
“…The simian virus 40-transformed newborn human kidney cell line NB-E (45), its derivative NB324K, and A9, a subline of mouse L cells (29), were grown in minimal essential medium (GIBCO), as were the human cervical carcinoma cell line HeLa, the spontaneously immortalized human keratinocytes HaCat (4), the simian virus 40-trans-formed human lung fibroblast line MRC5-V1 (26), the y-6'Cotransformed human fibroblast line KMST6 (33), and NHF-5, a normal, finite-life human foreskin fibroblast strain derived from a primary culture (infected at passage 4 or 5). Normal nondifferentiated human keratinocytes (NHK) were isolated from neonatal foreskins by the method of Tuynder et al (53). NHK cells were grown in (serum-free) keratinocyte-SFM medium (GIBCO) and infected at passages 1 or 2.…”
Section: Methodsmentioning
confidence: 99%
“…In the first study, radiation-transformed human fibroblasts formed foci in vitro and formed tumors in nude mice (14); in the second study, fibroblasts became immortal and underwent further spontaneous transformation after continuous culture (35,36). The third study reported that radiationtreated keratinocytes became immortal but not tumorigenic (42). Thus, 76R-30, together with its normal parent cell strain (76N), represents the first model of radiation-induced tumorigenic transformation of human mammary epithelial cells.…”
Section: S L 18smentioning
confidence: 99%
“…The (8,15). The status of p53 protein in other radiation-transformed human cells established by others has not been reported (14,36,42). However, a high incidence of p53 mutations has been observed in murine UV-and y-irradiation-induced tumors (26,30).…”
Section: S L 18smentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a few immortal human cell lines have been established from normal human cells in culture following repeated exposure to radiation or chemical mutagens. These include cell lines derived from diploid fibroblasts (14,15), mammary epithelial cells (25), and keratinocytes (29). In an attempt to identify a senescence or mortality gene(s) involved in normal diploid fibroblasts, we used two of these nontumorgenic immortalized human cell lines, KMST-6 (KMST) and SUSM-1 (SUSM), which were established from fetal human fibroblasts after repeated gamma irradiation and 4-NQO treatment, respectively (14,15).…”
mentioning
confidence: 99%